Magnetic Nanosystems as a Therapeutic Tool to Combat Pathogenic Fungi - Heba Salah Abbas; Akilandeswari Krishnan (Tabriz University of Medical Sciences, 2020)
The overuse of antibiotics is the main reason for the expansion of multidrug-resistant microorganisms, especially, pathogenic fungi, such as Candida albicans and others. Nanotechnology provides an excellent therapeutic tool for pathogenic fungi. Several reports focused on metal oxide nanoparticles, especially, iron oxide nanoparticles due to their extensive applications such as targeted drug delivery. Using biological entities for iron oxide nanoparticle synthesis attracted many concerns for being eco-friendly, and inexpensive. The fusion of biologically active substances reduced and stabilized nanoparticles. Recently, the advancement and challenges for surface engineered magnetic nanoparticles are reviewed for improving their properties and compatibility. Other metals on the surface nanoparticles can enhance their biological and antimicrobial activities against pathogenic fungi. Furthermore, conjugation of antifungal drugs to magnetic nanoparticulate increases their antifungal effect, antibiofilm properties, and reduces their undesirable effects. In this review, we discuss different routes for the synthesis of iron oxide nanoparticles, surface coating manipulation, their applications as antimicrobials, and their mode of action.